Fiscal policy and economic growth in Kenya - Daniel M'Amanja; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2005)
The question of whether or not fiscal policy stimulates growth has dominated theoretical and empirical debate for a long time. One viewpoint believes that government involvement in economic activity is vital for growth, but an opposing view holds that government operations are inherently bureaucratic and inefficient and therefore stifles rather than promotes growth. In the empirical literature, results are equally mixed. The aim of this paper is not to resolve the raging debate but to add to the fiscal policy-growth literature by examining the case of a small open developing country, Kenya. We used time series techniques to investigate the relationship between various measures of fiscal policy on growth on annual data for the period 1964 - 2002. Categorising government expenditure into productive and unproductive and tax revenue into distortionary and non-distortionary, we found unproductive expenditure and nondistortionary tax revenue to be neutral to growth as predicted by economic theory. However, contrary to expectations, productive expenditure has strong adverse effect on growth whilst there was no evidence of distortionary effects on growth of distortionary taxes. On the other hand, government investment was found to be beneficial to growth in the long run. These results should prove useful to policy makers in Kenya in formulating expenditure and tax policies to ensure unproductive expenditures are curtailed while at the same time boosting public investment.
Keywords: 330